2018
DOI: 10.1039/c7ra11720e
|View full text |Cite
|
Sign up to set email alerts
|

The study on continuous denitrification, desulfurization of pyrolusite/activated coke hybrid catalyst

Abstract: The SO2 removal and regeneration of ACP improved its NO removal activity, while the denitrification had almost no effect on the desulfurization. The metal sulfate of ACP-Rn showed catalytic activity for NO reduction although there is also a reverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…12 It is noteworthy that the content and type of Scontaining functional groups also developed during the C-S−R process. 12,24,25 In other words, in situ S-doping is induced by the C-S−R process. However, the impact of S-containing groups on the physicochemical properties and migration behavior of intrinsic sites has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 It is noteworthy that the content and type of Scontaining functional groups also developed during the C-S−R process. 12,24,25 In other words, in situ S-doping is induced by the C-S−R process. However, the impact of S-containing groups on the physicochemical properties and migration behavior of intrinsic sites has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Obviously, regeneration plays a crucial role in the long-term operation of an integrated removal system. 12,23 Li et al investigated the impact of the cyclic desulfurization and regeneration (C-S−R) process on denitration performance and proposed that the enhanced SCR activity could be attributed to the increase in O-containing groups. 12 It is noteworthy that the content and type of Scontaining functional groups also developed during the C-S−R process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration mainly removes the adsorbed pollutants through desorption and decomposition to restore the adsorption capacity of activated carbon. , The choice of regeneration technology is closely related to the type and characteristics of adsorbed substances. Research by Guilane and Hamdaoui reported that low-frequency ultrasonication could desorb 4-chlorophenol with a stable structure in EAC from petroleum and pharmaceutical wastewater and the regenerated activated carbon do not differ significantly with the virgin carbon . Liu et al investigated that the magnesium sulfate with a low melting point deposited on Mn-based EAC from coal-fired flue gas is decomposed under 650 °C thermal regeneration and the specific surface area is 800 m 2 /g .…”
Section: Introductionmentioning
confidence: 99%